The Charles H. Scott Gallery - Emily Carr College of Art & Design : 1984/85 Exhibitions. - Keziere, Robert; Emily Carr College of Art, Granville Island, Vancouver (Vancouver : Charles H. Scott Gallery, 1984)
Dikeakos, Alexandra ; Massé, Gloria ; Poole, Leslie ; Morgan, Joey ; Ross, Rick ; Prince, Richard ; Pitch, Marcia ; Grauer, Sherry ; Keziere, Robert ; etc.
overzicht tentoonstelling 1984-1985
English
boek